2018
DOI: 10.1021/acs.jpcc.8b06608
|View full text |Cite
|
Sign up to set email alerts
|

Developing Distinct Chemical Environments in Ionic Liquid Films

Abstract: We report the reversible transitions from two distinct chemical environments (interfacial and bulk) to a single, globally ordered dominant environment that extends to 800 nm, within two triflate-based ionic liquid (IL) films. Vibrational spectra for supported IL films exhibit multiple peaks for the same vibrational mode, indicating the presence of multiple chemical environments (interfacial and bulk) in the film. After a quiescent maturation time, the vibrational spectra show much simpler absorption profiles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…7,11–13 The Fayer group, in a series of elegant experiments using small molecules as probes, has identified organization with a persistence length on the order of tens to hundreds of nm in RTILs, 14–19 and the Shaw group has identified the evolution of structural order on the micrometer length scale in thin RTIL films. 20–23 Very recently, the Welton group has identified spatial variation in n , the refractive index, over distances of tens to hundreds of nm using Raman scattering. 24 It is clear from all these studies that RTILs exhibit structural order over length scales vastly in excess of what is typical for liquid phase solvents.…”
Section: Introductionmentioning
confidence: 99%
“…7,11–13 The Fayer group, in a series of elegant experiments using small molecules as probes, has identified organization with a persistence length on the order of tens to hundreds of nm in RTILs, 14–19 and the Shaw group has identified the evolution of structural order on the micrometer length scale in thin RTIL films. 20–23 Very recently, the Welton group has identified spatial variation in n , the refractive index, over distances of tens to hundreds of nm using Raman scattering. 24 It is clear from all these studies that RTILs exhibit structural order over length scales vastly in excess of what is typical for liquid phase solvents.…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, there is abundant evidence for structural organization and for the influence of charged surfaces on dynamics in RTILs. Most of these reports place such organization up to multiple tens of nanometers, ,, , and in some instances the organization is limited by the thickness of the RTIL films examined. Our group has found evidence for induced charge density gradients (ρ f ) in RTILs with a spatial extent of tens of micrometers. We discuss our findings and their implications below, with an eye toward understanding how the free charge density gradients we find may be influenced by structural organization in RTILs. One important consideration is that the structural order reported for thin RTIL films may exhibit longer-range effects in thicker samples, bringing structural organization and free charge density gradients into closer agreement.…”
Section: Charge Density Gradients In Rtilsmentioning
confidence: 80%
“…The Shaw group has found compelling evidence for long-range structural organization in ionic liquids. They formed thin RTIL films using a dynamic wetting technique and acquired FTIR, optical ellipsometry, and second harmonic generation measurements. The Shaw group monitored the (polarized) IRRAS spectra of BMIM + TFSI – thin films as a function of time (minutes to days) and observed the gradual changes of band positions and intensities for several bands in the 1000–1400 cm –1 region. While several of the bands did not change over time, there were four bands that were seen to exhibit changes in intensity and/or frequency.…”
Section: Organization In Rtilsmentioning
confidence: 99%
See 1 more Smart Citation
“…These researchers demonstrated that ionic liquids form long-rage ordered structures out to ∼2 μm from the solid surface over a time period up to 2 h after dewetting. In a following study, these same researchers proved the propagation of ordering at the solid–ionic liquid interface to form ordered extended structures and the role of shear as a disruptive force in such ordering …”
Section: Buried Interfacesmentioning
confidence: 95%